2018
DOI: 10.1007/s00198-018-4406-z
|View full text |Cite
|
Sign up to set email alerts
|

The utility of FRAX® in predicting bone fractures in patients with chronic kidney disease on hemodialysis: a two-year prospective multicenter cohort study

Abstract: FRAX® enables a better assessment of major bone fracture risk in ESRD patients undergoing hemodialysis than any of its components and other risk factors considered in the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Nutrients are directly linked to spine, hip and whole-body bone density in postmenopausal women [ 22 ] and patients on hemodialysis [ 23 , 24 ]. In contrast to previous study, a shorter duration of hemodialysis was inversely associated with vertebral fracture in this study [ 7 , 25 ]. Despite these observations, the duration of hemodialysis has not been consistently correlated with fracture.…”
Section: Discussioncontrasting
confidence: 99%
“…Nutrients are directly linked to spine, hip and whole-body bone density in postmenopausal women [ 22 ] and patients on hemodialysis [ 23 , 24 ]. In contrast to previous study, a shorter duration of hemodialysis was inversely associated with vertebral fracture in this study [ 7 , 25 ]. Despite these observations, the duration of hemodialysis has not been consistently correlated with fracture.…”
Section: Discussioncontrasting
confidence: 99%
“…e factors that influenced the higher FN BMD during CKD progression but did not influence LS BMD remain unclear. is result may be explained by the fact that the hip has more cortical bone than, which is more impaired compared to, trabecular of the bone in CKD patients [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…17 In patients with CKD, a recent study had reported that FRAX discriminated and predicted fractures. 21 However, whether the combination of clinical risk factors with BMD improves predictive discrimination is not clear. 22,23 Therefore, we tested whether combining a subset of the clinical risk factors in FRAX (age, sex, race, weight, height, family history of fracture, glucocorticoid use, and smoking history) with BMD at the total hip would improve fracture prediction.…”
Section: Discussionmentioning
confidence: 99%